2015
DOI: 10.1002/ccd.26383
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Coronary Artery Dissection

Abstract: In general, the long-term outcome of patients with SCAD is excellent, and medical therapy can be safely applied in the majority of patients. However, SCAD can be a life-threatening and sometimes catastrophic event, and some patients experience early or late complications including SCAD of another vessel. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 211 publications
(81 citation statements)
references
References 17 publications
1
75
2
3
Order By: Relevance
“…SCAD most commonly occurs in patients with few or no traditional cardiovascular risk factors. 810,13,16,29 Recent series using careful diagnostic criteria that exclude iatrogenic, traumatic, and atherosclerotic dissection 6 suggest that SCAD may be a cause of up to 1% to 4% of ACS cases overall 8,3032 (Table 1), occurs overwhelmingly in women, 8,11,13,30,31,33 may be the cause of ACS in up to 35% of MIs in women ≤50 years of age, 11,16,32 and is the most common cause of pregnancy-associated MI (43%) 17 (Table 2). Pregnancy-associated SCAD appears to make up a smaller proportion of overall SCAD than early case series suggest, 13,19,29,33,35 likely as a result of better detection of less severe SCAD among women who were not recently pregnant.…”
Section: Epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…SCAD most commonly occurs in patients with few or no traditional cardiovascular risk factors. 810,13,16,29 Recent series using careful diagnostic criteria that exclude iatrogenic, traumatic, and atherosclerotic dissection 6 suggest that SCAD may be a cause of up to 1% to 4% of ACS cases overall 8,3032 (Table 1), occurs overwhelmingly in women, 8,11,13,30,31,33 may be the cause of ACS in up to 35% of MIs in women ≤50 years of age, 11,16,32 and is the most common cause of pregnancy-associated MI (43%) 17 (Table 2). Pregnancy-associated SCAD appears to make up a smaller proportion of overall SCAD than early case series suggest, 13,19,29,33,35 likely as a result of better detection of less severe SCAD among women who were not recently pregnant.…”
Section: Epidemiologymentioning
confidence: 99%
“…6,8,11,13,30,31,33,36 One study reported that men presented with SCAD at a slightly younger age than women (mean age, 48.6 [SD, 9.8] years versus 52.3 [SD, 9.2] years; P =0.05). 37,38 Although SCAD has been reported in all major racial and ethnic groups, the majority of patients are white, a finding that may reflect referral and sampling bias and the demography of patients cared for at reporting centers.…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations